2009
DOI: 10.1016/j.joca.2009.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Macromer density influences mesenchymal stem cell chondrogenesis and maturation in photocrosslinked hyaluronic acid hydrogels

Abstract: Objective Engineering cartilage requires that a clinically relevant cell type be situated within a 3D environment that supports cell viability, the production and retention of cartilage-specific ECM, and eventually, the establishment of mechanical properties that approach that of the native tissue. In this study, we investigated the ability of bone marrow derived mesenchymal stem cells (MSCs) to undergo chondrogenesis in crosslinked methacrylated hyaluronic acid (HA) hydrogels (MeHA) of different macromer conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
178
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(193 citation statements)
references
References 43 publications
14
178
1
Order By: Relevance
“…In agreement with previous studies (Bian et al, 2013;Erickson et al, 2009), a denser, presumably stiffer, PCM also develops in the higher concentration hydrogels to which the MSCs can adhere and sense. In addition to a stiffer micro-environment for MSCs in the 4 % hydrogels, it is also reasonable to assume that the more developed PCM in these constructs leads to an increase in the number of integrin binding sites per cell.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous studies (Bian et al, 2013;Erickson et al, 2009), a denser, presumably stiffer, PCM also develops in the higher concentration hydrogels to which the MSCs can adhere and sense. In addition to a stiffer micro-environment for MSCs in the 4 % hydrogels, it is also reasonable to assume that the more developed PCM in these constructs leads to an increase in the number of integrin binding sites per cell.…”
Section: Discussionsupporting
confidence: 92%
“…Irrespective of hydrogel stiffness, this permissive medium did not support chondrogenesis of MSCs. As seen previously, when maintained in a medium supplemented with TGF-β3, cartilage matrix production was inhibited in stiffer hydrogels (Bian et al, 2013;Erickson et al, 2009). One potential explanation for this is that diffusivity of biomolecules (such as TGF-β3) would be lower in the stiffer, denser 4 % hydrogels; however, these hydrogels are still 96 % fluid and are therefore not expected to significantly inhibit biomolecule diffusivity.…”
Section: Discussionsupporting
confidence: 51%
“…Recent in vitro studies have demonstrated successful chondrogenesis of hMSCs photoencapsulated in HA hydrogels formed through cross-linking of HA modified with methacrylate groups (27)(28)(29). However, it still remains a challenge to recapitulate the functional properties of the native articular cartilage using only hMSCs, particularly compared with donor-matched articular chondrocytes, as shown in a bovine model (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…These gels support both human and bovine MSC chondrogenesis [12,17]. In this study, we used a 1% w/vol HA formulation that maximizes matrix formation by juvenile bovine MSCs [18]. Similar to pellets, bovine MSCs in this three-dimensional context were highly age-dependent with fetal and juvenile MSCs producing robust samples with compressive properties reaching approximately 20% of native tissue values within 3 weeks.…”
Section: Discussionmentioning
confidence: 99%